St.Vincent and the Grenadines : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
This consultation paper explains that in addition to the adverse impact of the global slowdown and higher commodity prices, St. Vincent and the Grenadines has been hit by two successive natural disasters in the last 12 months. As a result, real GDP has been contracted by a cumulative 4.7 percent since 2007 and is expected to remain slightly negative this year. Growth is expected to improve gradually toward its potential, but significant downside risks remain, largely related to developments in the global economy.